Emerging linked ecologies for a national scale retrofitting programme: The role of local authorities and delivery partners. (February 2020) - Wade, Faye; Bush, Ruth; Webb, Janette
Abstract: Energy Efficient Scotland (EES) is the Scottish Government's flagship programme for the national-scale retrofitting of buildings over the next 15–20 years. This is a critical component of Scotland's commitment to net zero greenhouse gas emissions by 2045, that will also help to reduce fuel poverty and improve local economies. The success of EES is reliant on partnerships between local authorities, arms-length external organisations, charities, and social enterprises. However, little is known about how these organisations collaborate for the delivery of building retrofit. This paper analyses interview data from local authorities and these delivery partners, conceptualising them as part of linked ecologies, or interconnected networks of professional groups. EES is identified as a hinge that holds distinct meanings for different parties; it supports learning between local authorities and delivery partners, but does not guarantee the alignment of priorities. The concept of avatars, or individuals and skills that travel between organisations, reveals the search for relevant internal knowledge amongst local authority officers, whilst external delivery partners amass expertise for retrofitting. To ensure successful national-scale building retrofit, policy makers will need to develop shared databases, and clear guidance for the allocation and distribution of resources and responsibilities between local authorities and delivery partners. Highlights: Local authorities and third sector organisations partner to deliver building retrofit. These influential middle actors form networks defined here as linked ecologies. Local authorities and delivery partners have differential expertise and priorities. Policy guidance should include clarity over division of responsibilities. Policy makers should develop shared building energy efficiency databases.